Space Science and Nation’s Development: Evaluating the Benefits of Space Science (Journal of Science, Technology and Innovation Policy, 2021)
Space science has a major role and giving impacts on our society for the last 50 years and will continue providing returns on the investment. The Return on Investment (ROI) could be in the form of new knowledge that provides an understanding to the world problem such that relating to the Earth-Sun relationship. These can be directly beneficial or indirectly one. Other than that space science will provide an economic opportunity as well as protecting us from massive destruction against asteroid impact of vast solar flare. This paper maps the space science benefits in the new of knowledge and strategic and in the same time projected future benefits.
Keywords: Space science; Return of Investment; Intangible benefits